KARAKTERISTIK TAFSIR AL-MARÄ€GHÄª DAN PENAFSIRANNYA TENTANG AKAL - Hadi, M. Khoirul (Hunafa: Jurnal Studia Islamika, 2014)
This article discusses the methodology of al-MarÄghÄ« interpretation, especially in a study about the ratio. Tafsir al-MarÄghÄ« has unique characteristics. This interpretation in the reviewer's favorite by using the adab al-ijtimÄâ€™Ä« method of interpretation, brief writing style, as well as terms that are easy to understand. Al-MarÄghÄ« intentionally omit discussion of non-essential, such as nahw-á¹£arf aspects, so that the reader does not get stuck on the text but the context of interpretation. In the problem of ratio, al-MarÄghÄ« have a better opinion of the group of theologians developed in the community, according to al-MarÄghÄ« sense capable of distinguishing between God's promise to the promise of Satan, reason can also believes in the afterlife after this life, this second opinion is not appears on the opinion of theologians before al-MarÄghÄ«.Kata Kunci: al-MarÄghÄ«, sistematik, adab al-IjtimÄâ€™Ä«. -SAï¿½;t ï¿½ï¿½:@ï¿½:/span>dakwah, komunikasi, perspektif Alquran ansiï¿½fgaï¿½ï¿½:@ï¿½:mso-fareast-language:EN-US;mso-bidi-language:AR-SA'>: Â Â Â Â Â Â  Corak, quasi-Obyektifis Tradisionalis, Obyektifis, quasi Obyektifis Modernis